2023
DOI: 10.3847/1538-4357/acb92e
|View full text |Cite
|
Sign up to set email alerts
|

Modest Dust Settling in the IRAS04302+2247 Class I Protoplanetary Disk

Abstract: We present new Very Large Array observations, between 6.8 and 66 mm, of the edge-on Class I disk IRAS04302+2247. Observations at 6.8 mm and 9.2 mm lead to the detection of thermal emission from the disk, while shallow observations at the other wavelengths are used to correct for emission from other processes. The disk radial brightness profile transitions from broadly extended in previous Atacama Large Millimeter/submillimeter Array 0.9 mm and 2.1 mm observations to much more centrally brightened at 6.8 mm and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…By resolving the asymmetry along the disk minor axis, the new high-resolution image presented here offers a strong constraint on the dust scale height. In addition, the value is consistent with an independent study that modeled another high-resolution image at Band 4 (Villenave et al 2023). On the other hand, the derived radius of R 0 = 310 au is consistent with past modeling efforts based on lower-resolution millimeter images in which the major axis of the disk was well resolved (Wolf et al 2003;Gräfe et al 2013).…”
Section: Continuum Forward Ray-tracingsupporting
confidence: 89%
See 1 more Smart Citation
“…By resolving the asymmetry along the disk minor axis, the new high-resolution image presented here offers a strong constraint on the dust scale height. In addition, the value is consistent with an independent study that modeled another high-resolution image at Band 4 (Villenave et al 2023). On the other hand, the derived radius of R 0 = 310 au is consistent with past modeling efforts based on lower-resolution millimeter images in which the major axis of the disk was well resolved (Wolf et al 2003;Gräfe et al 2013).…”
Section: Continuum Forward Ray-tracingsupporting
confidence: 89%
“…In one extreme, dust settled into an infinitely thin sheet should appear symmetric across the minor axis, and for disks with rings, the rings and gaps should not show azimuthal variation (e.g., Pinte et al 2016;Doi & Kataoka 2021). Several observations of Class II sources show that the dust is predominantly well settled (e.g., Andrews et al 2018;Long et al 2018;Villenave et al 2020;Doi & Kataoka 2021;Liu et al 2022;Villenave et al 2023). One of the clearest cases is SSTC2D J163131.2−242627 (or Oph 163131 for short), whose gaps are resolved even though the disk is nearly edge-on (Villenave et al 2022; i ∼ 84°).…”
Section: The Outer Cap Of 13 Comentioning
confidence: 99%
“…This indicates that the disk is slightly offset from edge-on, with the eastern side tilted toward us. Finally, previous studies also found that its millimeter emission is not significantly concentrated in the midplane (Lin et al 2023;Villenave et al 2023).…”
Section: Introductionmentioning
confidence: 59%
“…Furthermore, limited information is currently available regarding the timescale of vertical settling and its efficiency within younger systems, which still possess part of their primordial envelope. The recent results from the eDISK large program (Ohashi et al 2023) and two recent independent studies on the embedded disk IRAS04302+2247 (Lin et al 2023;Villenave et al 2023), indicated that large dust is not very settled in Class 0 and I systems. This suggests that most vertical settling of large (∼millimeter)-sized particles might occur between the Class I and Class II phases.…”
Section: Introductionmentioning
confidence: 99%
“…Our goal is a qualitative comparison of our results with ALMA observations of edge-on or almost edge-on protoplanetary disks. Specifically, the works of Villenave et al (2020Villenave et al ( , 2022Villenave et al ( , 2023 have shown that many protoplanetary disks appear settled in λ = 1.25 mm images obtained with ALMA. Oph 163131 is the most prominent example, with a very thin dust disk of height H d,100 au ≈ 0.5 au.…”
Section: Radiative Transfer Postprocessingmentioning
confidence: 99%